Neuroinflammation and the Kynurenine Pathway in CNS Disease: Molecular Mechanisms and Therapeutic Implications - Mithaiwala, Mustafa N. (Cells, 2021)
Diseases of the central nervous system (CNS) remain a significant health, social and economic problem around the globe. The development of therapeutic strategies for CNS conditions has suffered due to a poor understanding of the underlying pathologies that manifest them. Understanding common etiological origins at the cellular and molecular level is essential to enhance the development of efficacious and targeted treatment options. Over the years, neuroinflammation has been posited as a common link between multiple neurological, neurodegenerative and neuropsychiatric disorders. Processes that precipitate neuroinflammatory conditions including genetics, infections, physical injury and psychosocial factors, like stress and trauma, closely link dysregulation in kynurenine pathway (KP) of tryptophan metabolism as a possible pathophysiological factor that ‘fuel the fire’ in CNS diseases. In this study, we aim to review emerging evidence that provide mechanistic insights between different CNS disorders, neuroinflammation and the KP. We provide a thorough overview of the different branches of the KP pertinent to CNS disease pathology that have therapeutic implications for the development of selected and efficacious treatment strategies.